2022
DOI: 10.3389/fendo.2022.783150
|View full text |Cite
|
Sign up to set email alerts
|

Review of Mendelian Randomization Studies on Endometrial Cancer

Abstract: Endometrial cancer (EC) is a common gynecological cancer. In some parts of the world, the incidence and mortality of EC are on the rise. Understanding the risk factors of EC is necessary to prevent the occurrence of this disease. Observational studies have revealed the association between certain modifiable environmental risk factors and EC risk. However, due to unmeasured confounding, measurement errors, and reverse causality, observational studies sometimes have limited ability to judge robust causal inferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 151 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Obese women tend to have metabolic syndrome and comorbidities such as diabetes mellitus and hypertension, and polycystic ovary syndrome, which contribute to EC development [ 33 , 34 , 35 ]. Recent data from Mendelian randomization protocols have indicated that hypercholesterolemia with high low-density lipoprotein cholesterol levels, though a common finding in metabolic syndrome, has been shown to decrease EC risk [ 34 ]. Insulin growth factor 1 (IGF-1) has a negative effect on EC, increasing the risk of its occurrence.…”
Section: Classification Of Endometrial Cancermentioning
confidence: 99%
“…Obese women tend to have metabolic syndrome and comorbidities such as diabetes mellitus and hypertension, and polycystic ovary syndrome, which contribute to EC development [ 33 , 34 , 35 ]. Recent data from Mendelian randomization protocols have indicated that hypercholesterolemia with high low-density lipoprotein cholesterol levels, though a common finding in metabolic syndrome, has been shown to decrease EC risk [ 34 ]. Insulin growth factor 1 (IGF-1) has a negative effect on EC, increasing the risk of its occurrence.…”
Section: Classification Of Endometrial Cancermentioning
confidence: 99%
“…Endometrial cancer is one of the most common gynaecological cancers in high-income countries, 1 often presents at an early stage, 2 and is frequently associated with comorbidities. 3 In contrast to many other cancer types, the incidence and mortality of endometrial cancer are increasing worldwide, [4][5][6][7] at least in part because of the global obesity epidemic, 4 with elevated mortality rates also related to the decentralisation of treatment. 8,9 For many years, endometrial cancer care has been beset with poor outcomes for patients with advanced stage disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is currently possible to implement 2SMR studies for multiple exposures and outcomes thanks to the availability of public repositories that offer free access to the results of GWAS carried out in large patient cohorts [ 26 , 27 , 28 ]. This strategy has been fruitful in cancer [ 29 , 30 ] and nutritional research [ 31 ], as well as in the study of cardiovascular [ 32 , 33 ], immune-mediated [ 34 , 35 , 36 , 37 ], and neurological disorders [ 38 , 39 ], amongst others.…”
Section: Introductionmentioning
confidence: 99%